Efficacy of Interleukin 8 (IL-8) in the detection of urinary tract infection - Barnett, Jacqueline; Kiely, Janice; Luxton, Richard; Morris, Nicola; Drake, Marcus (Frontiers in Immunology, 2026)
IntroductionUrinary tract infection (UTI) is the most common bacterial infection independent of age. Currently, the gold standard for diagnosis of UTI is based on the presence of bacteria together with white blood cells in the urine to distinguish significant infection vs contamination. Unfortunately, white blood cell count in the urine is non-specific. An ideal biomarker should be elevated in all UTIs, irrespective of the causative organism, and remain low in the absence of infection or systemic inflammation. The purpose of this proof-of- concept study was to examine whether IL-8 could act as an efficacious biomarker for UTI infection in combination with confirmed bacterial infection.MethodsIn this study, IL-8 levels were measured in anonymised urine samples sent to the pathology laboratory for microbiology testing using commercially available ELISA kits. The urine samples tested had laboratory confirmed infection with Escherichia coli, Proteus, or Klebsiella bacteria.ResultsThe results demonstrated that although the IL-8 levels were variable for the 3 different causative agents of UTI tested, there was a significant difference between no growth samples and combined UTI samples. Of other biomarkers tested only lactoferrin gave comparable results to IL-8.DiscussionThe IL-8 data presented is consistent with other published work and suggests that testing for IL-8 with measurement of uropathogenic bacteria could be a sensitive screening test for an accurate diagnosis of active UTI infection, excluding contamination and systemic inflammation. Larger studies with integrated clinical data are necessary to explore this further.